Fused Imidazopyrazoles: Synthetic Strategies and Medicinal Applications - Rizk E. Khidre; Bakr F. Abdel-Wahab; Othman Y. Alothman (Journal of Chemistry)
The current review summarizes the known synthetic routes of fused imidazopyrazoles. This review is classified into two main categories based on the type of annulations, for example, annulation of the imidazole ring onto a pyrazole scaffold or annulation of the pyrazole ring onto an imidazole scaffold. Some medicinal applications of imidazopyrazoles are mentioned.